PENGARUH VOLUME PERDAGANGAN SAHAM, TINGKAT INFLASI DAN NILAI TUKAR TERHADAP VOLATILITAS HARGA SAHAM SUB SEKTOR BATU BARA YANG TERDAFTAR DI BURSA EFEK INDONESIA - Nia Wati; Ayu Puspitaningtyas (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2023)
This study aims to analyze the effect of stock trading volume, inflation rate and exchange rate on the volatility of stock prices in the coal, sub-sector listed on the Indonesia Stock Exchange. The population of this study is companies listed in the coal, sub-sector on the IDX for the 2011-2020 period. The sampling method used purposive sampling. The results showed that partially the volume of stock trading and the exchange rate had a significant positive effect on stock price volatility, while the inflation rate variable had a significant negative effect on stock price volatility. Trade volume, inflation rate and exchange rate simultaneously have a significant effect on stock price volatility.